2021
DOI: 10.3389/fnut.2021.739359
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Coffee and Risk of Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Objective: The results from epidemiologic studies on the relationship between intake of coffee and the risk of gestational diabetes mellitus (GDM) remain inconclusive. A meta-analysis was performed to achieve a comprehensive finding regarding the association between intake of coffee and the risk of GDM.Methods: PubMed, Scopus, ISI Web of Science, and Google Scholar were searched to find articles published up to August 2021. Observational studies that reported risk estimates [risk ratios (RRs), hazard ratios (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…As for the pattern of consumption of products that contain caffeine, those with the highest results were coffee (55.35%) and Coca-Cola (23.8%). Recent studies have shown that regular coffee intake can help fight chronic and degenerative diseases, such as Parkinson's disease and cardiovascular diseases [17-20], in addition to preventing Type 2 Diabetes Mellitus [21]. It was also observed that about 14.28% of the students consumed energy drinks, which can present a health risk, since these drinks have high levels of caffeine compared to other substances that compose it, such as taurine, caffeine, guarana, ginseng, glucuronolactone, and vitamins [22].…”
Section: Discussionmentioning
confidence: 99%
“…As for the pattern of consumption of products that contain caffeine, those with the highest results were coffee (55.35%) and Coca-Cola (23.8%). Recent studies have shown that regular coffee intake can help fight chronic and degenerative diseases, such as Parkinson's disease and cardiovascular diseases [17-20], in addition to preventing Type 2 Diabetes Mellitus [21]. It was also observed that about 14.28% of the students consumed energy drinks, which can present a health risk, since these drinks have high levels of caffeine compared to other substances that compose it, such as taurine, caffeine, guarana, ginseng, glucuronolactone, and vitamins [22].…”
Section: Discussionmentioning
confidence: 99%